IMPLEMENTATION OF LEAN MANAGEMENT PRINCIPLES IN HEALTHCARE ORGANIZATIONS - Mohammed Hamad Alhrbi, Abdullah Hamad Hamadan Almutairi, Mohammad Abdullah Mubarak Almarwan, Yasir sammar almutairi, Abdulrahman Abdullah Alghamdi, Abdullah Ahmed Alghamdi, Shaya Murayki Alruwaili, Badr AED Alotaibi, Alanazi‏ Hamad Ghathith,,; Abdullah Mushi Rashed Aldawsari, (Chelonian Research Foundation, 2022)
The primary objective of this paper was twofold: firstly, to develop a collaborative methodology that enables the implementation of lean management in healthcare using the action research approach; secondly, to demonstrate the effectiveness of this approach through implementing it to the sleep section of an academic medical center . This technique suggests the adoption of lean management in its most comprehensive form, including the incorporation of lean concepts and selected practical tools or practices to attain a competitive edge. When implementing lean management, modifications were introduced by considering the whole service value chain. This implementation entailed training and engaging staff in the endeavor (staff pillar), identifying and analyzing inefficiencies in value chain procedures (processes pillar), and implementing control and evaluation mechanisms aligned with objectives (key indicators of success pillar) while implementing improvement actions to attain these objectives. The use of this technique resulted in enhanced management of flow of patients in regards to efficiency, effectiveness, and quality, as well as an internal shift towards a lean culture. Keywords: lean management, lean healthcare, employee involvement